Optimization of single screw extrusion - Gaspar-Cunha, A. (2018)
Multi-objective evolutionary optimization algorithms (MOEA) are used for the optimization of plasticating single screw extrusion. For this purpose, a specific MOEA is linked to available process modelling routines. The methodology is used to set the operating conditions and identify the screw geometry for a specific case study, thus demonstrating the practical utility of this approach.